Storytelling and Story-Reading in Early Years : How to Tell and Read Stories to Young Children. - Medlicott, Mary (Jessica Kingsley Publishers, 2018)
Stories play a crucial role in young children's social and literacy development. This guide gives professionals the skills to plan and run the best possible storytelling and reading sessions for children, from how to use props and voices, to how to cater for mixed ability learning groups. Includes stories, rhymes and activities for ages 2-5.